2023
DOI: 10.1002/biot.202200477
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of wild Cressa cretica biomass for pectinase production from a halo‐thermotolerant bacterium

Abstract: Halophytes are the native inhabitants of saline environment. Their biomass can be considered as a potential substrate for the production of microbial enzymes. This study was intended at feasible utilization of a halophytic biomass, Cressia cretica, for pectinase production using a halo‐ and thermo‐tolerant bacterium, Bacillus vallismortis MH 10. The data from fractionation of the C. cretica biomass revealed presence of 17% pectin in this wild biomass. Seven different factors (temperature, agitation, pH, inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…We previously reported a similar method for the extraction of lignin, hemicellulose, pectin, and cellulose from sugarcane bagasse, and the components were examined using SEM and FTIR, confirming the composition and form of the components. [ 2 ] Hassan et al [ 29 ] used a similar method to extract components from the halophytic plant C. cretica . In this study, the outcome of the fractionation process (Table 1) showed a higher cellulose content (44% w/w) in P. karka biomass than in C. cretica and S. fruticosa which also shared a similar lignin content (6% w/w).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported a similar method for the extraction of lignin, hemicellulose, pectin, and cellulose from sugarcane bagasse, and the components were examined using SEM and FTIR, confirming the composition and form of the components. [ 2 ] Hassan et al [ 29 ] used a similar method to extract components from the halophytic plant C. cretica . In this study, the outcome of the fractionation process (Table 1) showed a higher cellulose content (44% w/w) in P. karka biomass than in C. cretica and S. fruticosa which also shared a similar lignin content (6% w/w).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to utilizing cheap raw materials, improving substrate conversion, and shortening production time, increasing fermentation temperature is also an effective way to reduce production costs. [13,14] Because a large amount of heat is released during industrial fermentation, large amounts of cooling water are usually used to cool down the fermentation process to keep the temperature constant. The optimum fermentation temperatures for most γ-PGA-producers, including Bacillus subtilis, B. licheniformis, and B. amyloliquefaciens, were 30-37 • C. [5,[15][16][17] If the fermentation temperature can be properly raised, the production cost can be reduced as the use of cooling water can be reduced.…”
mentioning
confidence: 99%